Acute Stress Assessment From Excess Cortisol Secretion: Fundamentals and Perspectives - Boucher, Patrice; Plusquellec, Pierrich (Frontiers in Endocrinology, 2019)
Our paper aims to redefine the concept of stress in the context of maintaining allostasis; the term has been reserved for situations that concomitantly involve established physiological and psychological stress components. In particular, we analyze how novelty, unpredictability, threat to the ego, and low sense of control challenge allostasis. The concept of stress is then related to a state of difficulty in maintaining allostasis, rather than referring to the overall body response to the situation. This state of difficulty may be observed either in planning the strategy to deal with the situation, evaluating consequent target trajectories for the actuators, the catabolic mediators and the activators, or regulation of the biological systems through these trajectories. Catabolic mediator excesses are proposed as scaling the level of difficulty in maintaining allostasis. The excess proportion of cortisol load (EPCL) is consequently proposed to scale the stress level. A first proof-of-concept of this indicator is realized using the Physiostress dataset, by asserting that it is, as predicted from its theoretical basis, more in phase with the stress level expected from the nature of the task and participant-reported stress compared to common indicators based on the cortisol response magnitude itself.